2016
DOI: 10.1016/j.jagp.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Identification Deficits, Cognitive Decline, and Dementia in Older Adults

Abstract: Several recently developed biomarkers of Alzheimer disease (AD) are invasive, expensive, and difficult to obtain in most clinical settings. Olfactory identification test performance represents a noninvasive, inexpensive biomarker of AD that may have predictive accuracy comparable with neuroimaging measures and biomarkers assessed in cerebrospinal fluid. Neurofibrillary tangles in the olfactory bulb are among the earliest pathologic features of AD and are also seen in the projection pathways from the olfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 42 publications
4
56
0
2
Order By: Relevance
“…Recent studies have established anosmia as a prodromal biomarker for Alzheimer's disease (48)(49)(50) and the presence of olfactory deficits in a subset of MS patients correlating with symptom severity (51,52). GAS-infected mice show severe persistent physiological deficits in M/ T neuronal function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established anosmia as a prodromal biomarker for Alzheimer's disease (48)(49)(50) and the presence of olfactory deficits in a subset of MS patients correlating with symptom severity (51,52). GAS-infected mice show severe persistent physiological deficits in M/ T neuronal function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two found that the association between OI and mortality was lowered when controlling for dementia, yet remained statistically significant. Of note, OI was shown to be associated with future cognitive decline in cognitively intact subjects (Devanand, 2016). Moreover, there is evidence of existing post-mortem markers of neurodegenerative disease in the brain of subjects without previous clinical signs of MCI or AD (Wilson et al, 2009).…”
Section: Associated Neurodegenerative Diseasesmentioning
confidence: 99%
“…It is known that approximately 70% of MCI patients will ultimately convert to AD (Gauthier et al, 2006). Yet, recent data converge toward the idea that olfactory-impaired MCI patients are more prone to develop AD than those without OI (Conti et al, 2013;Devanand, 2016;Adams et al, 2018;Jung et al, 2019). Overall, these findings make OI a potential early predictor for AD development.…”
Section: Introductionmentioning
confidence: 94%
“…The oral‐nasal‐olfactory system is regarded as a direct portal for bacterial pathogens to the brain, and olfactory system dysfunction leads to neurodegeneration. Olfactory dysfunction is present in up to 90% of patients with AD; the olfactory bulb neurofibrillary tangles are among the earliest pathologic features of AD and human and animal behavioral studies provide indication that olfactory dysfunction can occur early in the AD process, even at a preclinical stage …”
Section: Helicobacter Pylori and Ad Linkage: Main Hypothesismentioning
confidence: 99%